Perlindungan Hukum Bioetik Dan Medikolegal Pada Kasus Bayi Tabung - Sumanti, Betsi (PMIH Untag Semarang, 2024)
Based on existing laws in Indonesia, the IVF implementation program itself refers to Law Number 36 of 2009 which discusses health, which was later updated with Law Number 17 of 2023. This Law explains that the implementation of the IVF program must be carried out in accordance with with legal, religious, moral and civility norms. Problems arise if they do not provide appropriate results and ultimately trap medical personnel in a legal crisis that is very unpleasant and causes time, material and psychological losses that often drag on for a long time. In theory, IVF technology provides an opportunity for married couples to know the gender and genetic abnormalities that may occur in the embryo, so as to avoid the possibility of implantation of a defective embryo. The results of this research show that IVF or in medical language called In Vitro Fertilization (IVF) is an attempt to obtain pregnancy by bringing together sperm cells and egg cells in a special container. The legal and policy framework governing IVF has been regulated in Law Number 17 of 2023 and Minister of Health Regulation Number 43 of 2015 concerning the Implementation of Artificial Reproductive Technology, which contains: general provisions, licensing, guidance and supervision, transitional provisions and closing provisions. Bioethical and medicolegal legal protection in cases of IVF is important to ensure that reproductive technology is used ethically and in accordance with legal principles and human rights. This also helps protect the interests of the patient and the welfare of the child born through the procedure